Internally generated memory testing: results of repeated test administration. - Baker T; Graybeal L; Barrett A (Experimental Aging Research)
A critical memory skill rarely clinically tested is the ability to remember self-generated material. Healthy aged participants (n = 30; Experiment 1) and pilot participants with probable Alzheimer disease (pAD) (n = 9; Experiment 2) were twice administered a memory test including both internally generated and externally supplied items for recall. Healthy aged participants were biased to recall internally originating over externally supplied material on first, but not second, presentation. However, pAD participants demonstrated internal bias during both sessions. The pAD participants were also specifically impaired when told to remember internal material. This study provides further evidence that internally originating items can be used to assess memory. In pAD, memory for internal material with specific attempt to remember may be selectively impaired.